Indigenizing the North American Model of Wildlife Conservation - Mateen A. Hessami; Ella Bowles; Jesse N. Popp; Adam T. Ford (Canadian Science Publishing, 2021)
Although a diversity of approaches to wildlife management persists in Canada and the United States of America, the North American Model of Wildlife Conservation (NAM) is a prevailing model for state, provincial, and federal agencies. The success of the NAM is both celebrated and refuted amongst scholars, with most arguing that a more holistic approach is needed. Colonial rhetoric permeates each of the NAM's constituent tenets-yet, beyond these cultural and historical problems are the NAM's underlying conservation values. In many ways, these values share common ground with various Indigenous worldviews. For example, the idea of safeguarding wildlife for future generations, utilizing best available knowledge to solve problems, prioritizing collaboration between nations, and democratizing the process of conserving wildlife all overlap in the many ways that the NAM and common models of Indigenous-led conservation are operationalized. Working to identify shared visions and address necessary amendments of the NAM will advance reconciliation, both in the interest of nature and society. Here, we identify the gaps and linkages between the NAM and Indigenous-led conservation efforts across Canada. We impart a revised NAM-the Indigenizing North American Model of Wildlife Conservation (I-NAM)-that interweaves various Indigenous worldviews and conservation practice from across Canada. We emphasize that the I-NAM should be a continuous learning process that seeks to update and coexist with the NAM, but not replace Indigenous-led conservation.